Analisis Tingkat Daya Tahan Aerobik Atlit Renang Science Swimming Team - Muhammad Faizal Budiman; Mokhamad Nur Bawono (Mutiara Pendidikan dan Olahraga, 2025)
Swimming performance is strongly influenced by aerobic endurance, which enables athletes to maintain speed, technique efficiency, and physiological stability during prolonged activity. However, quantitative data regarding aerobic endurance levels among club-level swimmers in Indonesia remain limited. This study aimed to describe the aerobic endurance level of athletes from the Science Swimming Team. A descriptive research design was employed involving 11 swimmers selected through purposive sampling. Data were collected using the Cooper Swimming Test conducted over a 15-minute freestyle swimming session, and aerobic capacity was estimated through VO₂max values. The collected data were analyzed descriptively to classify aerobic endurance levels based on established normative categories by sex and age. The findings indicated that most athletes achieved good to very good performance in swimming distance; however, VO₂max classifications showed that aerobic capacity was predominantly in the moderate category, with only one female athlete reaching an excellent level. This disparity suggests that favorable distance performance does not necessarily reflect optimal aerobic capacity. The results imply the need for more targeted training programs focusing on improving VO₂max through structured aerobic and interval-based training. These findings provide practical input for coaches in designing data-driven and individualized training strategies to enhance aerobic endurance and competitive performance in swimming athletes.